MANAJEMEN PENDIDIKAN KEDISIPLINAN SANTRI DI PONDOK PESANTREN AL-QUR’ANIYYAH MAJALENGKA - kholil baehaqi; YUYUD ASPIYUDIN (Insitut Pesantren Babakan cirebon, 2024)
These researches used are, First, to description of plan of education disciplinary students in Nurussalam Islamic Boarding School Sidogede.. Secondly, to description of implementation of education disciplinary students in in Nurussalam Islamic Boarding School Sidogede.Third,to description of monitoring of education disciplinary students in Nurussalam Islamic Boarding School Sidogede. This research used a qualitative approach with case study, and the data collection used by interview, observation, and documentation, Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions or verification, than informant of this research are guidance of students and students The results of the research are: 1) Planning: planning the goals of disciplinary education for students according to the vision, mission, and goals of the At Nurussalam Islamic Boarding School Sidogede. ; making disciplinary rules for students; making guidelines for violations and penalties that will be given to disciplinary violators; and setting a schedule for disciplinary activities for students. 2) Implementation: providing direction for student discipline education; motivating students to participate in student discipline education; leading the course of student discipline education; communicating with students to ensure student discipline education understanding; and making decisions on actions that violate student discipline. 3) Supervision: direct supervision includes court and attendance readings; indirect supervision includes performance evaluation. Keywords: Management, Education, Management Of Education, and Dicipline Students.